Tracer Tomography: Design Concepts and Field Experiments Using Heat as a Tracer. Issue 1 (13th November 2014) - Doro, Kennedy O.; Cirpka, Olaf A.; Leven, Carsten
Abstract Numerical and laboratory studies have provided evidence that combining hydraulic tomography with tomographic tracer tests could improve the estimation of hydraulic conductivity compared with using hydraulic data alone. Field demonstrations, however, have been lacking so far, which we attribute to experimental difficulties. In this study, we present a conceptual design and experimental applications of tracer tomography at the field scale using heat as a tracer. In our experimental design, we improve active heat tracer testing by minimizing possible effects of heat losses, buoyancy, viscosity, and changing boundary conditions. We also utilize a cost‐effective approach of measuring temperature changes in situ at high resolution. We apply the presented method to the 8 m thick heterogeneous, sandy gravel, alluvial aquifer at the Lauswiesen Hydrogeological Research Site in Tübingen, Germany. Results of our tomographic heat‐tracer experiments are in line with earlier work on characterizing the aquifer at the test site. We demonstrate from the experimental perspective that tracer tomography is applicable and suitable at the field scale using heat as a tracer. The experimental results also demonstrate the potential of heat‐tracer tomography as a cost‐effective means for characterizing aquifer heterogeneity.